2016
DOI: 10.1371/journal.pone.0154123
|View full text |Cite
|
Sign up to set email alerts
|

A Patient Friendly Corifollitropin Alfa Protocol without Routine Pituitary Suppression in Normal Responders

Abstract: The release of corifollitropin alfa simplifies daily injections of short-acting recombinant follicular stimulating hormone (rFSH), and its widely-used protocol involves short-acting gonadotropins supplements and a fixed GnRH antagonist regimen, largely based on follicle size. In this study, the feasibility of corifollitropin alfa without routine pituitary suppression was evaluated. A total of 288 patients were stimulated by corifollitropin alfa on cycle day 3 following with routine serum hormone monitoring and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Moreover, daily injection of gonadotropins are needed in the aforementioned down-regulation protocols. Wang et al [ 35 ] proposed a patient-friendly corifollitropin alfa protocol using GnRH antagonist occasionally only when serum LH was ≧ 6 IU/L to reduce injections as much as possible. However, this method needs frequent blood withdrawals to monitor hormone levels for timely initiation of antagonist injection once LH rose above 6 IU/L, which is inconvenient and stressful on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, daily injection of gonadotropins are needed in the aforementioned down-regulation protocols. Wang et al [ 35 ] proposed a patient-friendly corifollitropin alfa protocol using GnRH antagonist occasionally only when serum LH was ≧ 6 IU/L to reduce injections as much as possible. However, this method needs frequent blood withdrawals to monitor hormone levels for timely initiation of antagonist injection once LH rose above 6 IU/L, which is inconvenient and stressful on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were from the outpatient department of a private fertility center (Hsinchu, Taiwan). The patients underwent individualized stimulation protocols for IVF/ICSI ( Wang et al , 2016 ; Hwang et al , 2018 ). The blastocysts used in the study were surplus embryos from patients who achieved successful live births.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless, few studies have reported that reducing the GnRH-ant dose to as little as 0.125–0.2 mg per day is also equally effective (1214). Wang et al even reported that routine GnRH-ant administration was not required, as 87.2% of the patients did not need any antagonist throughout the stimulation cycle (15). Thus, the minimum possible dose of GnRH antagonist that is suitable for IVF-ET remains controversial.…”
Section: Introductionmentioning
confidence: 99%